Extraction Techniques for Bioactive Compounds and Antioxidant Capacity Determination of Chilean Papaya (Vasconcellea pubescens) Fruit. (5th May 2015) - Uribe, Elsa; Delgadillo, Alvaro; Giovagnoli-Vicuña, Claudia; Quispe-Fuentes, Issis; Zura-Bravo, Liliana
Abstract : The aim of this work was to assess and compare different extraction methods by using high hydrostatic pressure (HHPE), ultrasound (UE), agitation (AE), and their combinations for the extraction of bioactive compounds of Chilean papaya. Extract antioxidant capacity was evaluated by three methods (i.e., DPPH, FRAP, and Voltammetry) and phenolic compounds and vitamin C were determined by HPLC. Papaya sample extraction was performed by HHPE at 500 MPa for 10 min and UE and AE for 30 min, respectively. The combined-extractions: HHPE-UE and HHPE-AE, were carried out for 5 min and 15 min, respectively. The highest values found were total phenolic 129.1 mg GAE/100 g FW, antioxidant capacity by DPPH 20.6 mM TE/100 g FW, and voltammetry 141.0 mM TE/100 g FW for HHPE-UE method in free compound extraction. Regarding vitamin C content, its highest value was found by HHPE-UE (74 mg/100 g FW) a combined extraction method. The phenolic compounds rutin and p -coumaric acid were found in all the extracts, both in free and bound forms, respectively. Besides, the combined techniques improved the extraction of bioactive compounds.